Progressive Salafism in Online Fatwa - Rusli, R. (Al-Jamiah: Journal of Islamic Studies, 2014)
This paper deals with the construction of progressive Salafism in online fatwa, particularly in the site of Islam Online. This website is established by YÅ«suf al-QarÄá¸ÄwÄ« and his colleagues within the European Council for Fatwa and Research, which has been influenced by reformist-salafists, such as al-ShawkÄnÄ«, al-AfghÄnÄ«, âAbduh, and Riá¸Ä, who underline the role of text and modernity. The siteâs approach is progressive-substantialist (combining teks and reality), which is built on the principles of Islamic law on minorities (fiqh al-aqalliyyÄt), like taysÄ«r (facilitation), wasaá¹iyyah (moderation), and iâtidÄl (equilibrium), that are seen as universal values contributing to the creation of a global-pluralist society. Because of its moderate nature, the language used by the site tends to emphasize not on prohibiting and labelling âhereticâ, but on a solution to the problems people encounter. In relation to socio-political language, the concept of ummah is understood in an inclusive way. Ummah is built and based on the principles of belief (Ä«mÄn) and Islam, and tied by the solidarity of the Quranic messages about Islamic monotheism (tawá¸¥Ä«d) and divine justice (âadl). The concept of ummah refers to the Quranic concepts such as ummah wasaá¹ or ummah muqtaá¹£idah, which means âmoderate communityâ.[Artikel ini membahas tentang konstruksi Salafisme progresif dalam fatwa online, terutama situs Islam Online. Website ini didorong oleh YÅ«suf al-QarÄá¸ÄwÄ« dan para koleganya dalam European Council for Fatwa and Research, yang dipengaruhi oleh salafi-reformis, seperti al-ShawkÄnÄ«, al-AfghÄnÄ«, âAbduh, dan Riá¸Ä, yang menghargai teks dan modernitas. Pendekatan situs ini adalah progresif-substansialis (menggabungkan teks dan realitas), yang dibangun pada prinsip-prinsip fikih minoritas (fiqh al-aqalliyyÄt), seperti taysÄ«r (memberikan kemudahan), wasaá¹iyyah (moderat), dan iâtidÄl (keseimbangan),yang dilihat sebagai nilai-nilai universal yang memberikan kontribusi bagi penciptaan masyarakat global yang pluralis. Karena watak modernnya, bahasa yang digunakan oleh situs ini cenderung tidak menekankan pada pengharaman dan pelabelan âbidahâ, namun menekankan pada solusi terhadap masalah-masalah yang dihadapi masyarakat. Terkait dengan bahasa sosial-politik, konsep umat dipahami dalam cara yang inklusif. Umat didasari pada prinsip iman dan Islam, dan diikat oleh solidaritas pesan Alquran tentang monoteisme Islam (tawá¸¥Ä«d) dan keadilan (âadl). Konsep umat mengarah kepada konsep Alquran seperti ummah wasaá¹ atau ummah muqtaá¹£idah, yang berarti âkomunitas yang moderatâ.]